2004
DOI: 10.2135/cropsci2004.1218
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Designation of Quantitative Trait Loci for Seed Protein, Seed Oil, and Seed Weight from Two Soybean Populations

Abstract: In soybean [Glycine max (L.) Merr.], there is limited and inconsistent information on the confirmation of previously reported QTL. The objectives of this study were to: (i) confirm previously reported QTL for seed protein, seed oil, and seed weight in an independent population of PI97100 × ‘Coker 237’ with the same RFLP markers and (ii) verify previously reported QTL in an independent population of ‘Young’ × PI416937 for the same seed traits using SSR markers mapped in the same region as the original RFLP mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 30 publications
9
72
1
6
Order By: Relevance
“…According to the Soybase (2008), 76 QTL have been identified and reported as related to protein content. However, little consistency has been observed for QTL expressed in different environments or different populations (Brummer et al, 1997;Fasoula et al, 2004;Panthee et al, 2005). In the present study, this fact might be explained by the high genotype vs. environment interaction observed and by the fact that these QTL can be considered environmentally sensitive (Brummer et al, 1997).…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…According to the Soybase (2008), 76 QTL have been identified and reported as related to protein content. However, little consistency has been observed for QTL expressed in different environments or different populations (Brummer et al, 1997;Fasoula et al, 2004;Panthee et al, 2005). In the present study, this fact might be explained by the high genotype vs. environment interaction observed and by the fact that these QTL can be considered environmentally sensitive (Brummer et al, 1997).…”
Section: Resultscontrasting
confidence: 61%
“…Mapping and QTL detection studies for protein content in seeds have been reported extensively in literature (Chung et al, 2003;Fasoula et al, 2004;Hyten et al, 2004;Panthee et al, 2005). However, many reported QTL have still to be confirmed and their consistency validated (Fasoula et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este tipo de associação foi comum para a maioria dos QTL mapeados por Zhang et al (2004), que detectaram QTL que influenciam, ao mesmo tempo, até cinco características agronômicas distintas. Esse efeito pleiotrópico explica a correlação genética negativa existente entre os teores de óleo e proteína em soja (Fasoula et al, 2004).…”
Section: Resultsunclassified
“…Vários marcadores de locos de caracteres quantitativos (QTL) foram relatados para teores de óleo e proteína em soja (Sebolt et al, 2000;Csanádi et al, 2001;Specht et al, 2001;Chung et al, 2003;Chapman et al, 2003;Tajuddin et al, 2003;Fasoula et al, 2004;Hyten et al, 2004;Zhang et al, 2004;Panthee et al, Pesq. agropec.…”
Section: Introductionunclassified